Development characteristics and controlling factors of dolomite reservoirs of permian Qixi a Formation in central Sichuan Basin - Tan, Kaijun; Wu, Qingpeng; Chen, Juan; Yao, Jun; Qin, Yang; Zhang, Yongfeng (Frontiers in Earth Science, 2023)
In recent years, with the fine exploration of carbonate reservoirs in the Qixia Formation, central Sichuan Basin, researchers have made important oil and gas discoveries in the dolomite reservoirs. However, the characteristics, genesis and controlling factors of dolomite reservoirs in the Qixia Formation in this area are still unclear. In this paper, the petrology, pore structures, physical properties and geochemical characteristics of the dolomite reservoirs in the Permian Qixia Formation in the central Sichuan Basin have been systematically studied based on a large number of cores, thin sections, physical property and geochemical tests. Furthermore, the genesis and main controlling factors of dolomite reservoirs are clarified. The study shows that the dolomites have the characteristics of small single-layer thickness and multi-layer development, and they are usually interbeded with the limestones. The reservoir types are mainly fine crystal and fine medium crystal dolomite, and the reservoir spaces include intercrystalline pores and dissolution pores (or caves). Moreover, the reservoir physical properties are characterized by medium porosity and medium to high permeability. Quasi-syngenetic dolomitization is the main origin of dolomite in the target layer, and the dolomite was slightly modified by hydrothermal solution at the end of the Maokou Formation period. The development of dolomite reservoirs in the Qixia Formation in the study area is affected by palaeogeomorphology, sedimentation and diagenesis. The granular shoal facies developed in the high parts of the paleogeomorphology provides the material basis for the formation of dolomite reservoirs. The high frequency sequence interface controls the development of dolomite reservoirs in the highstand systems tract. In addition, the quasi-syngenetic dissolution promots the development of the early secondary pores and provids an effective channel for the migration of the diagenetic fluids in the later stage. In the direction of orthogonal horizontal deposition, the dolomites have the characteristics of thin monolayer thickness, multiple sequences and are interbedded with limestone. The dolomite shoals in the study area are distributed as clumps in the plane, which has great potential for hydrocarbon exploration.